2020
DOI: 10.15326/jcopdf.7.4.2020.0142
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cathelicidin is Independently Associated with Reduced Lung Function in COPD: Analysis of the Subpopulations and Intermediate Outcome Measures in COPD Study Cohort

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Two clinical studies (n = 2/19, 11% of all clinical studies included in the review) reported the negative correlation of cathelicidin in plasma [ 42 ] and sputum [ 43 ] with lung function. Both sputum and plasma cathelicidin levels were found to be negatively correlated with lung function [ 42 , 43 ]. Both findings, conducted by Burkes at al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two clinical studies (n = 2/19, 11% of all clinical studies included in the review) reported the negative correlation of cathelicidin in plasma [ 42 ] and sputum [ 43 ] with lung function. Both sputum and plasma cathelicidin levels were found to be negatively correlated with lung function [ 42 , 43 ]. Both findings, conducted by Burkes at al.…”
Section: Resultsmentioning
confidence: 99%
“…Both findings, conducted by Burkes at al. and Wright et al, have to be seen as especially thorough, as they derive from clinical studies with a high number of participants, namely exceeding 500 [ 42 ] and 100 individuals [ 43 ]. Furthermore, one study conducted by Jiang et al (5%, n = 19) noted that increased induced sputum LL-37 levels in COPD patients were also associated with airflow limitation [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found a negative correlation between sputum SLPI and beta defensin-1 and FEV1. Recently, cathelicidin has also been found to negatively correlate with FEV1 in stable COPD patients, 28 highlighting the potential for these AMPs to identify patients at greater risk of lung function decline.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few studies on COPD stratification based on exacerbation risk shows that the LL-37 is lower in high-risk exacerbators compared to low-risk counterparts ( 361 , 366 , 367 ). Similarly, COPD stratification based on severity shows that LL-37 is significantly reduced in severe disease compared to mild/moderate disease ( 296 , 348 ). Several authors argue that this observation is most likely driven by a high background of NF-kB activation in severe disease, which has been reported to inhibit LL-37 ( 366 ).…”
Section: Antimicrobial Peptides and Lung Damage In Microbiome-immune ...mentioning
confidence: 96%
“…Besides the known protective effects of LL-37 against invading pathogens at the mucosa, several studies have implicated this peptide in COPD ( 289 , 315 , 336 , 337 , 337 , 338 , 338 , 339 , 339 , 340 , 340 , 341 , 341 , 342 , 342 , 343 , 343 , 344 , 344 , 345 , 345 , 346 , 346 351 ). Investigators have demonstrated its association with poor lung function ( 348 , 349 ). In a setting of cigarette-smoke exposure, low levels of LL-37 have been independently associated with lower FEV 1.…”
Section: Antimicrobial Peptides and Lung Damage In Microbiome-immune ...mentioning
confidence: 99%